Structured feedback and operative video debriefing with critical view of safety annotation in training of laparoscopic cholecystectomy: a randomized controlled study - Cizmic, Amila; Häberle, Frida; Wise, Philipp; Müller, Felix; Gabel, Felix; Mascagni, Pietro; Namazi, Babak; Wagner, Martin; Hashimoto, Daniel A.; Madani, Amin; Alseidi, Adnan; Hackert, Thilo; et al. (Surgical endoscopy and other interventional techniques, 2024)
The learning curve in minimally invasive surgery (MIS) is lengthened compared to open surgery. It has been reported that structured feedback and training in teams of two trainees improves MIS training and MIS performance. Annotation of surgical images and videos may prove beneficial for surgical training. This study investigated whether structured feedback and video debriefing, including annotation of critical view of safety (CVS), have beneficial learning effects in a predefined, multi-modal MIS training curriculum in teams of two trainees.
Online veröffentlicht: 23. April 2024
Gesehen am 10.10.2024